Inheritance Rights of The Youngest Child In The Middle Barumun Indigenous Community From The Perspective of Islamic Law - Rahmawati Siregar, Lili; Khair, Nispul; Tanjung, Dhiauddin (Journal of Law, Politic and Humanities, 2024)
This study aims to examine the determination of inheritance for the youngest child in the Central Barumun customary society from the perspective of Islamic law. The customary tradition of Central Barumun has its own rules and customs in the distribution of inheritance which is sometimes different from the provisions of Islamic law. This research uses field research (filed research) with a case study approach, collecting data through interviews with traditional leaders, indigenous people, naposo bulung adat and local religious leaders, then using data collection methods that are reviewed by observation, and related documents. The results showed that in the customary society of Central Barumun adheres to the inheritance distribution system with the descent system by giving automatically given to adult sons, and for the youngest child often gets special treatment in the distribution of inheritance and done by parents during life. If there is any remaining inheritance, it will be distributed after the parents die. Girls will not get the inheritance if it is not given by their brothers. Although in the view of Islamic Law the division carried out by the system cannot be called the division of inheritance, as stated in the Koran as the main guide to inheritance law in Islam which has determined the portion of each heir in accordance with the provisions that have been determined from Allah SWT, with a predetermined size based on the small and large age and has been confirmed by Islamic inheritance law stipulates that every time there is a death, the determination of the share of each heir must be done.